The impact of virtual exchange on East–West social relations: lessons from a China-Portugal foreign language exchange - Rienties Bart; Rets Irina (Journal of China Computer-Assisted Language Learning)
Student collaboration has always been integral to the learner journey. The current limited opportunities for face-to-face discussions and student mobility due to the pandemic have heightened the need for such online intercultural collaboration initiatives like Virtual Exchange (VE). At the same time, few studies have looked at collaboration patterns between Asian and Western students, while using robust mixed methods research design (i.e., pre-post TPACK, foreign language competence, diaries) and social network analysis. To that end, this study explored an East-West VE of 10 weeks between 16 university students from China and 18 students from Portugal working together online on shared tasks. The study compared the perceived development of technological and foreign language skills between the two groups of students, the extent to which their reported lived experiences in VE were positive for all students, as well as looked at the kind of relations the students developed with each other over the length of the exchange. The study provides important pedagogical implications for educators willing to design VE for the benefit of all students, as well as methodological implications for the use of social network analysis with VE data.